1962
DOI: 10.1111/j.1399-3054.1962.tb08126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Opening of the Stomatal Cells

Abstract: The effcfl of loiupenitiire on the stoinntjtl nioveim'nls lias been studied by about ten different workers (iiiriu}^ the p;ist 40 years. Some of the.se mveslij,'ations -amon^ them one oC mine iStaUeit H(28) -were made early in tbis period, al a time when it was not known that the movements are sensitive even to small water deficits in the leaves, and to sUj^ht chanj,'es in the (X)j content of the air. (Consequently, the experiments were made under conditions that may bave given rise In a water deficit, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 6 publications
4
20
0
Order By: Relevance
“…OnGuard2 faithfully reproduced the experimentally determined kinetics and dependence of stomatal aperture and g s on VPD and water availability, notably a weak dependence on VPD unless water delivery to the leaf was limited; it replicated the curvilinear effects of leaf temperature on aperture and g s (Supplemental Figure 1) previously reported across a range of species in the literature (Wilson, 1948;Stalfelt, 1962;Farquhar and Sharkey, 1982;Spence et al, 1984;Urban et al, 2017); it showed the opposing changes in guard cell osmolarity and turgor (Figure 2) expected of a unified framework equating VPD to extracellular osmotic potential; and it recapitulated previously published data of enhanced Mal synthesis and accumulation with osmotic stress (Asai et al, 1999(Asai et al, , 2000. Noteworthy to these predictions, within OnGuard2 it is the change in water potential of the apoplast around the guard cell with a VPD step that drives water flux across the guard cell plasma membrane, thereby affecting guard cell volume, the free concentration of solute within the guard cell, and engaging changes in ion transport and metabolism (Figure 8).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…OnGuard2 faithfully reproduced the experimentally determined kinetics and dependence of stomatal aperture and g s on VPD and water availability, notably a weak dependence on VPD unless water delivery to the leaf was limited; it replicated the curvilinear effects of leaf temperature on aperture and g s (Supplemental Figure 1) previously reported across a range of species in the literature (Wilson, 1948;Stalfelt, 1962;Farquhar and Sharkey, 1982;Spence et al, 1984;Urban et al, 2017); it showed the opposing changes in guard cell osmolarity and turgor (Figure 2) expected of a unified framework equating VPD to extracellular osmotic potential; and it recapitulated previously published data of enhanced Mal synthesis and accumulation with osmotic stress (Asai et al, 1999(Asai et al, , 2000. Noteworthy to these predictions, within OnGuard2 it is the change in water potential of the apoplast around the guard cell with a VPD step that drives water flux across the guard cell plasma membrane, thereby affecting guard cell volume, the free concentration of solute within the guard cell, and engaging changes in ion transport and metabolism (Figure 8).…”
Section: Discussionsupporting
confidence: 60%
“…The model also demonstrated a dependence on temperature (Supplemental Figure 1) that is broadly consistent with the curvilinear relationships previously reported for stomatal aperture across a number of species (Wilson, 1948;Stalfelt, 1962;Spence et al, 1984;Willmer and Fricker, 1996;Urban et al, 2017).…”
Section: Onguard2 Predicts a Steep Dependence Of G S At Limiting Hydrsupporting
confidence: 67%
“…1) may partially explain the rapid decrease in stomatal aperture in Vicia above 35 C (17). The effects of temperature on stomatal opening are complex, of course, and would not be explained by the response of this one enzyme alone.…”
Section: Discussionmentioning
confidence: 99%
“…2), since the general consensus of opinion (e.g. Stalfelt, 1962;Willmer and Mansfield, 1970) is that stomatai opening is mediated by an active process, requiring an energy source. One would assume, therefore, that higher temperatures would result in a greater degree of opening.…”
Section: Discussionmentioning
confidence: 99%